The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/14783363.2015.1059272
|View full text |Cite
|
Sign up to set email alerts
|

Key performance indicators measurement in service business: a fuzzy VIKOR approach

Abstract: This study attempts, through focusing on the concept of strategic control and by using fuzzy VIsekriterijumska Optimizacija i KOmpromisno Resenje (VIKOR) technique, to measure the importance and priority of key performance indicators (KPIs) in a successful service business of LG 'Goldiran Customer Service Company'. Based on the balanced score card, the KPIs in the four perspectives were determined and, by employing fuzzy multiple criteria decision-making (FMCDM) techniques, a systematic approach to help manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Some of the recent publications are summarized as follows. Sofiyabadi et al [17] use fuzzy logic to measure the importance and priority key performance indicators. Tyagi et al [20] analyze the enablers in order to implement a flexible supply chain performance measurement system using fuzzy decision-making trial-and-evaluation laboratory approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the recent publications are summarized as follows. Sofiyabadi et al [17] use fuzzy logic to measure the importance and priority key performance indicators. Tyagi et al [20] analyze the enablers in order to implement a flexible supply chain performance measurement system using fuzzy decision-making trial-and-evaluation laboratory approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, Opricovic and Tzeng [80] compared VIKOR with the Preference Ranking Organization METHod for Enrichment Evaluations (PROMETHEE), ELimination and Choice Expressing REality (ELECTRE), and TOPSIS. Öztayşi and Sürer [81] used uzzfy VIKOR for supply chain performance measurement. Sofiyabadi et al [81] apply fuzzy VIKOR in prioritizing key performance indicators in service sector.…”
Section: Fuzzy Vikormentioning
confidence: 99%
“…Öztayşi and Sürer [81] used uzzfy VIKOR for supply chain performance measurement. Sofiyabadi et al [81] apply fuzzy VIKOR in prioritizing key performance indicators in service sector. In the SEZ prioritization problem, it is more likely that the judgment of the decision-makers (DMs) is vague.…”
Section: Fuzzy Vikormentioning
confidence: 99%
“…The result elucidated that private banks had higher performance levels than foreign banks. Sofiyabadi et al (2016) evaluated the service business sectors by fuzzy VIKOR and BSC. From the combination of these two methods and the implementation in the company LG they concluded that this company should focus on the perspectives customer, learning and growth.…”
Section: Balanced Scorecardmentioning
confidence: 99%